Key variables for sustainable mangrove ecosystem management based on Scylla spp. in Banten Bay, Indonesia - ADITYA RAHMAN KINTU NIHAN; CECEP KUSMANA; MAJARIANA KRISANTI; TATANG TIRYANA; YAYA IHYA ULUMUDDIN (Society for Indonesian Biodiversity, 2025)
Abstract. Nihan ARK, Kusmana C, Krisanti M, Tiryana T, Ulumuddin YI. 2025. Key variables for sustainable mangrove ecosystem management based on Scylla spp. in Banten Bay, Indonesia. Biodiversitas 26: 2467-2484. Mangrove forests are crucial ecosystems that significantly contribute to achieving several of the United Nations' Sustainable Development Goals (SDGs), particularly SDG 13 (Climate Action), SDG 14 (Life Below Water), and SDG 15 (Life on Land). These ecosystems provide vital services, including carbon sequestration and coastal protection, and are home to species such as Scylla spp., critical for fisheries and local biodiversity. Mangroves contribute significantly to climate change mitigation by sequestering carbon at rates that exceed those of some terrestrial forests while also protecting coastal areas from erosion and severe weather phenomena. Mangrove habitats also support local economies through fisheries, wood products, and ecotourism, which align with SDGs 8 (Decent Work and Economic Growth) and 12 (Responsible Consumption and Production). However, concerns such as overexploitation and progressive habitat destruction endanger these ecosystems. This study examines the key variables that influence the sustainable management of Scylla spp. populations in a mangrove ecosystem in Banten Bay, Indonesia. This study employed the Matrix of Crossed Impact Multiplications Applied to a Classification (MICMAC) technique to analyze the ecological, economic, social, and institutional factors influencing the management of mangrove ecosystems. The results underscore the importance of collaboration, education, community engagement, and a strong regulatory framework in securing the long-term viability of mangrove ecosystems. The study highlights that Scylla spp. has both ecological and economic significance, and sustainable management of this species can incentivize local people to participate in conservation initiatives. Linking conservation efforts to the economic benefits of Scylla spp. allows for the reconciliation of ecological integrity with community well-being. The study highlights critical areas of intervention that can be addressed to enhance coastal communities' environmental sustainability and socio-economic well-being. The study provides practical recommendations for policymakers and environmentalists to manage mangrove ecosystems sustainably.